Level of CYP4G19 Expression Is Associated with Pyrethroid Resistance in Blattella germanica - Guang-zhou Guo; Yi-jie Geng; Da-na Huang; Cai-fang Xue; Ren-li Zhang (Journal of Parasitology Research)
German cockroaches have become a large problem in the Shenzhen area because of their pesticide resistance, especially to pyrethroid. A pyrethroid called “Jia Chong Qing” to prevent pests for a long time were found to be resistant to “Jia Chong Qing” with resistance index of 3.88 measured using RT-PCR and immunohistochemistry analysis showed that both CYP4G19 mRNA and CYP4G19 protein expression levels in the wild strain were substantially higher than that of a sensitive strain. dsRNA segments derived from the target gene CYP4G19 were prepared using in vitro transcription and were microinjected into abdomens of the wild strain. Two to eight days after injection, the result showed that CYP4G19 mRNA expressions were significantly reduced in the groups injected with dsRNAs.